Ammonia emissions after trailing hose application of digestates and cattle slurry - Norah Efosa; Christoph Häni; Thomas Kupper; Hans-Martin Krause; Johan Six; Else K. Bünemann (Nutrient Cycling in Agroecosystems, 2025)
Anaerobic digestion (AD) is a promising technique for waste management, producing energy and contributing to nutrient recycling in agroecosystems. While digestates have higher plant-available nutrient contents, they may be prone to increased ammonia (NH 3 ) losses due to elevated pH values and ammonium contents. This study investigates NH 3 emissions from an agricultural digestate consisting of cattle slurry, solid manure and food processing waste (SLA) and a municipal organic waste digestate (LID) applied alongside untreated cattle slurry (SLU) as a reference to maize and cereals with a trailing hose. Values of dry matter, ammoniacal nitrogen (TAN) and pH were higher for SLA and LID than for SLU. Emissions were determined in five application events over three years with NH 3 concentration measurements using an impinger system combined with backward Lagrangian Stochastic dispersion modeling. On average, 31%, 42%, and 43% of applied TAN volatilized as NH 3 from SLU, SLA, and LID, respectively. Despite being higher from the treatments, these differences were not statistically significant. Therefore, it remains unclear whether digestates differ in NH 3 emissions from untreated slurry. This topic needs further investigation due to the increasing use of AD.

Assessment of whole-site methane emissions from anaerobic digestion plants: Towards establishing emission factors for various plant configurations - Viktoria Wechselberger; Marlies Hrad; Marcel Bühler; Thomas Kupper; Bernhard Spangl; Anders Michael Fredenslund; Marion Huber-Humer; Charlotte Scheutz (Waste Management, 2025)

Dry and wet periods determine stem and soil greenhouse gas fluxes in a northern drained peatland forest - Reti Ranniku; Ülo Mander; Jordi Escuer-Gatius; Thomas Schindler; Priit Kupper; Arne Sellin; Kaido Soosaar (Science of The Total Environment, 2024)

Validation of a short-range dispersion and deposition model using field-scale ammonia and methane release experiments - Christoph Häni; Albrecht Neftel; Christophe Flechard; Christof Ammann; Alex Valach; Thomas Kupper (Agricultural and Forest Meteorology, 2024)

Feed-forward and noise-tolerant detection of feature homogeneity in spiking networks with a latency code - Michael Schmuker; Rüdiger Kupper; Ad Aertsen; Thomas Wachtler; Marc-Oliver Gewaltig (Biological Cybernetics, 2021)

The frequency distribution of lead concentration in feathers, blood, bone, kidney and liver of golden eagles Aquila chrysaetos: insights into the modes of uptake - Lukas Jenni; Milena M. Madry; Thomas Kraemer; Jacqueline Kupper; Hanspeter Naegeli; Hannes Jenny; David Jenny (Journal of Ornithology, 2015)

CXCR4 pathway associated with family history of melanoma - Wen-Qing Li; Jiali Han; Hans R. Widlund; Mick Correll; Yaoyu E. Wang; John Quackenbush; Martin C. Mihm; Alvaro Laga Canales; Shaowei Wu; Todd Golub; Yujin Hoshida; David J. Hunter; et al. (Cancer Causes & Control, 2014)

Brominated Flame Retardants in Fish of Lake Geneva (Switzerland) - Zeinab Cheaib; Dominique Grandjean; Thomas Kupper; Luiz F. de Alencastro (Bulletin of Environmental Contamination and Toxicology, 2009)